2004
DOI: 10.1299/jsmea.47.581
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Kidney Stone Fragmentation by Short Pulse Impingement

Abstract: In this work, numerical analyses are performed to study the behavior of stresses generated inside a kidney stone by direct pulse impingement during extracorporeal shock wave lithotripsy (ESWL), which leads to fragmentation of the stone. LS-DYNA, an explicit Finite Element code for non-linear dynamic analysis is employed to model the problems. Effects of pulse duration and acoustic property of the stone on stress field evolution inside the stone are studied for the pulse duration of 0.5 to 5.0 µs and two acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…In particular for the studies here we found that the passage of the shock wave in the fluid surrounding the stone generated shear waves or surface waves at the "equatorial" surface of the stone which propagated into the stone and interfered constructively with other waves to generate the peak stresses. This conflicts with the conclusions of Mihradi et al 11 that the classical spall or Hopkinson effect is responsible for the peak tensile stresses in the stone. The probable explanation for this is that the waveform they used did not have a short shock front and as we show in Fig.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In particular for the studies here we found that the passage of the shock wave in the fluid surrounding the stone generated shear waves or surface waves at the "equatorial" surface of the stone which propagated into the stone and interfered constructively with other waves to generate the peak stresses. This conflicts with the conclusions of Mihradi et al 11 that the classical spall or Hopkinson effect is responsible for the peak tensile stresses in the stone. The probable explanation for this is that the waveform they used did not have a short shock front and as we show in Fig.…”
Section: Discussioncontrasting
confidence: 96%
“…Cleveland and Tello 10 described a FDTD model for calculating pressure waves in kidney stones subject to lithotripsy shock waves but the model treated the stone as a fluid and neglected the presence of shear waves. Mihradi et al 11 employed a finite-element model ͑FEM͒ to predict the stress loadings on kidney stones in lithotripsy. The incident waveform was modeled as a half-sinusoid of purely positive pressure and simulations were carried out for pulses of different durations ͑0.5 to 5 s͒ in a two-dimensional Cartesian coordinate system.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, spalling (Xi and Zhong 2001; Mihradi et al 2004), cavitation (Zohdi and Szeri 2005) and shear wave stress (Cleveland and Sapozhnikov 2005) have been shown to depend critically on the size or geometry of the stone. Furthermore, acoustic pulse energy E eff (Koch and Grunewald 1989; Granz and Köhler 1992; Delius et al 1994; Eisenmenger 2001) and peak average pressure ( P +(avg) ) incident on the stone (Smith and Zhong 2012) are two of the lithotripter field parameters that have been correlated with SC.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant blast waves may not entirely be detrimental to us. A biomedical application such as the lithotripter shock wave technique, that uses the concept of concomitant shock waves to fragment kidney stones, has already been in use for the betterment of humankind . The severity of head injuries caused by the concomitant blast wave is generally related to the peak overpressure and pulse duration of the incident blast pulse and the incoming direction of blast relative to the sagittal axis of the head.…”
Section: Introductionmentioning
confidence: 99%